Hubungan Antara Penggunaan Gadget Terhadap Kualitas Tidur Siswa SMA Pertiwi - Indra Indra; Arif Al Hakim; Alvino Dwi Putra (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
This study aims to analyze the relationship between gadget usage and sleep quality among high school students at SMA Pertiwi Medan. Excessive gadget use, especially before bedtime, is often associated with sleep pattern disturbances that can affect students' sleep quality. This research employs a quantitative method with a descriptive correlational approach. Data were collected through questionnaires involving 100 students selected using random sampling techniques. The results show a significant relationship between the duration and frequency of gadget use and students' sleep quality. The higher the intensity of gadget use, the lower the quality of sleep experienced by students. Factors such as usage time, types of activities on gadgets, and sleep duration also influenced the findings. These results provide important implications for students, teachers, and parents to regulate gadget usage